2‐Methylimidazole‐assisted Morphology Modulation of a Copper‐based Metal‐organic Framework Transducer for Enhanced Electrochemical Peroxidase‐like Activity. Issue 1 (22nd September 2021) - Li, Junji; Liu, Zi‐Xuan; Li, Yi‐Xuan; Shu, Guofang; Zhang, Xue‐Ji; Marks, Robert S.; Shan, Dan
Abstract: A tailored metal‐organic framework transducer material Cu−BDC(NH2 )@2‐MI was synthesized with 2‐methylimidazole as competitive ligand for the modulation of its morphology and catalytic activity. 2‐MI effectively helped the deprotonation of 2‐aminoterephthalic acid and enabled the fast generation of MOF crystals at room temperature. More importantly, this 2‐MI‐doped MOF exhibited well‐tuned morphology and was able to assist efficient redox procedures in electrochemical H2 O2 reduction. Therefore, a prototype H2 O2 sensor can present decent linear ranges from 10 μM to 13.28 mM and a detection limit of 0.97 μM. This novel design could boost the utilization of proprietary MOFs materials out of laboratory. Abstract :